Mekanisme Penetapan Hak Atas Tanah Dan Penataan Tanah Terlantar Dilihat Dari Peraturan Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 4 Tahun 2010 - Marta, Andhyka; Idham, Idham (Universitas Medan Area, 2021)
Article 1 of the UUPA No. 5 of 1960 explains that the entire earth, water and space, including the natural resources contained therein in the territory of the Republic of Indonesia as a gift from God Almighty in the form of earth, water and space, are national assets. Land is a gift from God Almighty given to humans to be managed, used and maintained as well as possible as a source of life and livelihood. Land abandonment is an act that is unwise, uneconomical with the intention of losing the economic potential of the land, is unfair, and is a violation of the obligations that must be carried out by rights holders or parties who have obtained the basis for land tenure. The author uses a normative juridical approach as the type of research used with the details of the research used is descriptive analysis. The data collection technique used is literature study. The author uses data analysis, namely qualitative data analysis. To develop the use of land in Indonesia, the National Land Agency enacted Regulation of the Head of the Land Agency Number 4 of 2010 which regulates procedures for controlling abandoned land.